Listening differently: A pedagogy for expanded listening. (31st October 2017) - Gallagher, Michael; Prior, Jonathan; Needham, Martin; Holmes, Rachel
Abstract : Mainstream education promotes a narrow conception of listening, centred on the reception and comprehension of human meanings. As such, it is ill‐equipped to hear how sound propagates affects, generates atmospheres, shapes environments and enacts power. Yet these aspects of sound are vital to how education functions. We therefore argue that there is a need to expand listening in education, and suggest that listening walks could provide a pedagogy for this purpose. Using interview data in which early years practitioners reflect on a listening walk, we show how the method can: (i) produce heightened multisensory experiences of spaces; (ii) generate forms of difficulty and discomfort that produce new learning; and (iii) influence practice, particularly practitioners' ability to empathise with young children. Listening walks function by disrupting everyday sensory habits, provoking listeners to listen anew to their own listening, in an open‐ended way that is not tied to predetermined learning outcomes. The method therefore has wider pedagogic potential for rethinking education and childhood beyond rationality, representation and meaning.